Research progress on remote ischemic conditioning for improving prognosis of patients with acute ischemic stroke - Liyan Ren; Junyi Cui; Lu Sun; Lihua Zhou; Chunru Han; Shuyu Ma; Shouru Xue; Linqing Ma (Biochemistry and Biophysics Reports)
Acute ischemic stroke is a serious global health burden which has high disability and mortality rates. Remote ischemic conditioning, a non-intrusive treatment method, triggers a series of biochemical reactions and enhances the brain's resilience to ischemia-reperfusion injury by applying brief, reversible ischemic stimuli to the limbs. Remote ischemic conditioning offers neuroprotection by lowering oxidative stress, deterring neuronal apoptosis, inhibiting inflammation, protecting mitochondrial function, and preserving the blood–brain barrier. Clinical studies have confirmed that remote ischemic conditioning improves neurological recovery, reduces infarct volume, and enhances prognosis. However, the type of remote ischemic conditioning, intensity, frequency, duration, location, and equipment types vary considerably. Furthermore, the clinical application of remote ischemic conditioning faces some challenges, such as developing standardized treatment plans, evaluating long-term effects and safety, and exploring personalized and optimized treatments. However, the precise mechanisms of remote ischemic conditioning remain complex, requiring further research. Further study should concentrate upon elaborating the peculiar molecular and cellular mechanisms of remote ischemic conditioning, developing an optimal, evidence-based standardized treatment plan, and evaluating its clinical feasibility through extensive, longstanding follow-up trials. In the future, remote ischemic conditioning may play a greater role in the treatment of acute ischemic stroke, optimize patient prognosis, and enhance living quality.